Gênero e políticas feministas, o lado Sul - Scavone, Lucila [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Este artigo trata da questão do Feminismo no Brasil e das políticas feministas em relação à reprodução, seus impasses e avanços. Trata destas políticas sob a ótica das teorias de gênero, que analisam os paradoxos das reivindicações da igualdade universal com base nas diferenças. Busca elementos para compreender estas questões nas sociedades democráticas emergentes do sul, no caso específico, na sociedade brasileira.

This article concerns the Feminism in Brazil and also de feminist politics connected to procreation, its impasses and advances. The text deals with these politics trough gender theories, which analyze the paradoxes of demands for universal equality based on differences. The aim is to chase elements to understand these questions inside the emergent democratic societies from the south, in this specific case, in the Brazilian society.
Gender and feminist politics, the southern side
Keywords: Democracy and Gender; Brazilian Feminisms; Feminist Politics; Equality and Difference; Procreation Rights; Democracia e Gênero; Feminismos no Brasil; Políticas Feministas; Igualdade e Diferença; Direitos Reprodutivos